Levels of specific DNA fragments in the blood and their association with stages of melanoma. (1st February 2020) - Calbet‐Llopart, N.; Potrony, M.; Tell‐Martí, G.; Carrera, C.; Barreiro, A.; Aguilera, P.; Podlipnik, S.; Puig, S.; Malvehy, J.; Puig‐Butillé, J.A.
Summary: Blood plasma contains DNA fragments from dying cells, called cell‐free circulating DNA (cfDNA). In cancer patients, a fraction of their blood cfDNA comes from dying tumour cells. Therefore, key genetic alterations (mutations) from tumours might be detected in plasma from cancer patients. The analysis of cfDNA is a promising tool for the treating cancer patients, since the information from the tumour might be obtained from a blood sample, avoiding the use of 'invasive' methods such as tissue biopsies (samples taken by surgery, for example). Melanoma is an aggressive type of skin cancer. Each year more than 250, 000 new cases are diagnosed worldwide. The p.V600E mutation in the BRAF gene ( BRAF V600E ) is detected in approximately 50% of melanomas. Currently, the analysis of the BRAF V600E mutation in plasma from melanoma patients can be used to monitor their disease progression. Besides tumours, the BRAF V600E mutation is frequently detected in moles on the skin, which are a risk factor to developing melanoma. To date, no information exists about the role of dying cells from moles in the detection of BRAF V600E in plasma. This study, from Spain, aimed to assess the robustness of the BRAF V600E test in plasma. The authors analysed plasma from 146 people without melanoma and from 33 melanoma patients with BRAF V600E melanomas. Melanomas are categorized from stage I to stage IV, with stage 1 as the earliest melanoma and stage IV as the most advanced. Stage I and II melanomas are present in the skin only and have not spread elsewhere in the body. Stage III have spread towards or have reached the draining lymph glands (nodes) and Stage IV melanomas are those that have spread beyond the closest draining lymph glands to other parts of the body. In this study, cell‐free circulating BRAF V600E was detected in 71% of patients with stage IV melanoma and 15% with stage III, whereas it was only detected in 1.4% of people without melanoma. The results of the BRAF V600E test in an individual were not influenced by the number of moles they had or clinical characteristics of moles (such as an unusual appearance). Additionally, they observed that melanoma patients with advanced disease showed a higher amount of BRAF V600E in plasma. Altogether, these findings indicate that the BRAF V600E test is an effective and robust tool for use with melanoma patients. This summary relates to the study: Detection of cell‐free circulating BRAF V600E by droplet digital polymerase chain reaction in patients with and without melanoma under dermatological surveillance